The Association Between Body Mass Index and the Prevalence, Severity, and Frequency of Low Back Pain: Data From the Osteoarthritis Initiative. Issue 12 (15th June 2018) - Su, Charles A.; Kusin, David J.; Li, Samuel Q.; Ahn, Uri M.; Ahn, Nicholas U.
Abstract : Study Design: Cross-sectional study. Objective: To determine whether there is an association between body mass index (BMI) and the prevalence, severity, and frequency of low back pain and identify other potential patient risk factors for the development of low back pain. Summary of Background Data: Many studies have implicated that a high BMI is a risk factor for low back pain. However, few studies have examined the association between increased BMI and the prevalence, severity, and frequency of low back pain. Methods: Data from the Osteoarthritis Initiative, a multicenter, prospective study of knee osteoarthritis, were used to conduct this study, which included 4796 patients. BMI was categorized according to the World Health Organization classification and the prevalence, severity, and frequency of low back pain were assessed. Logistic regression was performed to identify additional patient risk factors associated with low back pain. Results: The prevalence of low back pain was found to be significantly higher in patients with an elevated BMI compared to those with normal or underweight BMI and demonstrated a stepwise increase with each BMI category. Approximately 47.4% of patients with normal or underweight BMI complained of low back pain compared with 72.8% of morbidly obese patients ( P  < 0.0001). No association was seen between BMI and the frequency or severity of low back pain episodes. Osteoarthritis of the back and depression were patient variables found to be associated with all three measures (prevalence, severity, and frequency) of low back pain. Conclusion: Elevated BMI is strongly associated with an increased prevalence of low back pain. Depression and osteoarthritis of the back are associated with the prevalence, severity, and frequency of low back pain. Level of Evidence: 3